3(x-10)-4=-6x-2

Simple and best practice solution for 3(x-10)-4=-6x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-10)-4=-6x-2 equation:


Simplifying
3(x + -10) + -4 = -6x + -2

Reorder the terms:
3(-10 + x) + -4 = -6x + -2
(-10 * 3 + x * 3) + -4 = -6x + -2
(-30 + 3x) + -4 = -6x + -2

Reorder the terms:
-30 + -4 + 3x = -6x + -2

Combine like terms: -30 + -4 = -34
-34 + 3x = -6x + -2

Reorder the terms:
-34 + 3x = -2 + -6x

Solving
-34 + 3x = -2 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-34 + 3x + 6x = -2 + -6x + 6x

Combine like terms: 3x + 6x = 9x
-34 + 9x = -2 + -6x + 6x

Combine like terms: -6x + 6x = 0
-34 + 9x = -2 + 0
-34 + 9x = -2

Add '34' to each side of the equation.
-34 + 34 + 9x = -2 + 34

Combine like terms: -34 + 34 = 0
0 + 9x = -2 + 34
9x = -2 + 34

Combine like terms: -2 + 34 = 32
9x = 32

Divide each side by '9'.
x = 3.555555556

Simplifying
x = 3.555555556

See similar equations:

| x-17=-12 | | -1=11+n | | 9x-13=-10+12x | | 9x-13=-10+12z | | x^16-2x^15-x^14+4x^13-x^11+x^10=0 | | 1-n=-2 | | -72=-18a | | (-x+4)(2x-1)= | | 12x^2-52x+35=0 | | 19k=-95 | | (45x^4y^10)/(9x^6y^6) | | 13=9x-5 | | 55-3T=103-7T | | 8x^2+60x-25=0 | | -14-x=-9 | | -117=-13m | | 195=13n | | -4(7-2q)+9q= | | m+14=21 | | 4n-18=42 | | (x+8)(x-2)=-24 | | 9x+9=9(x-4) | | p(p+8)=-7 | | 7n=-98 | | 1100=5c*2 | | 4(5x+8)=20x+32 | | -12=m-(-5) | | 2z/-9=-4 | | 1half+3=6 | | 1+4sinx=0 | | 3t^2+23t=8 | | 10+x-3x^2=0 |

Equations solver categories